Supporting the transition to net-zero emissions: The evolving role of central banks - Karen McGuinness (Bank of Canada, 2023)
While climate change was largely tackled by government policies in the past, central banks are increasingly grappling with the risks climate change poses. They are evaluating their operational policies to reflect these risks and the transition to a net-zero economy. This paper explores the trade-offs and considerations central banks face.
Keywords: D53; E58; E63; G32; Q54; 330; Central bank research; Climate change; Financial markets